2015
DOI: 10.1073/pnas.1520032112
|View full text |Cite|
|
Sign up to set email alerts
|

HIF-1 regulates CD47 expression in breast cancer cells to promote evasion of phagocytosis and maintenance of cancer stem cells

Abstract: Increased expression of CD47 has been reported to enable cancer cells to evade phagocytosis by macrophages and to promote the cancer stem cell phenotype, but the molecular mechanisms regulating CD47 expression have not been determined. Here we report that hypoxia-inducible factor 1 (HIF-1) directly activates transcription of the CD47 gene in hypoxic breast cancer cells. Knockdown of HIF activity or CD47 expression increased the phagocytosis of breast cancer cells by bone marrow-derived macrophages. CD47 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
266
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(276 citation statements)
references
References 62 publications
9
266
1
Order By: Relevance
“…Reported previously by us and others (60,61), SIRPα expression in macrophages is decreased following LPS stimulation, suggesting a dynamic nature for the CD47-SIRPα-mediated inhibition especially on infection or activation of TLR. The expression of CD47 on cells can also be changed under different conditions (62)(63)(64). Also reported by us, alteration of clustering structures of SIRPα on macrophages or CD47 on tissue cells affects phagocytosis (65,66).…”
Section: Discussionmentioning
confidence: 76%
“…Reported previously by us and others (60,61), SIRPα expression in macrophages is decreased following LPS stimulation, suggesting a dynamic nature for the CD47-SIRPα-mediated inhibition especially on infection or activation of TLR. The expression of CD47 on cells can also be changed under different conditions (62)(63)(64). Also reported by us, alteration of clustering structures of SIRPα on macrophages or CD47 on tissue cells affects phagocytosis (65,66).…”
Section: Discussionmentioning
confidence: 76%
“…Hypoxic signaling can promote resistance to T cell–mediated killing by increasing the expression of programmed death–ligand 1 (PD-L1) on tumor cells and myeloid-derived suppressor cells (MDSCs), and by enhancing CTLA-4 expression on CD8 + T cells, respectively [reviewed in ( 57 )]. Additionally, hypoxic tumor cells evade innate immune recognition through the up-regulation of CD47, a cell surface molecule that interacts with signal regulatory protein alpha (SIRP α) on the surface of macrophages to block phagocytosis ( 58 ).…”
Section: Mechanisms Of Hif-mediated Metastasismentioning
confidence: 99%
“…In hypoxic breast cancer cells, HIFs activate the transcription of target genes that play important roles in tumor growth, angiogenesis, metabolic reprogramming, motility, invasion, metastasis, and resistance to chemotherapy (15,16). Recent studies have demonstrated that HIFs are required for the specification and/or maintenance of BCSCs in response to hypoxia (17)(18)(19)(20)(21) or chemotherapy (22,23), leading to direct or indirect transcriptional regulation of genes encoding the pluripotency factors NANOG, SOX2, and KLF4. In addition, HIF-1α is required for hypoxia-induced epithelial-mesenchymal transition (24), which is also linked to the BCSC phenotype (25).…”
mentioning
confidence: 99%